The gift - Patterson, James, 1947-; Rust, Ned. (New York : Grand Central Pub., 2012)
After escaping imprisonment by the totalitarian regime known as the New Order, siblings Wisty and Whit Allgood, who possess magical powers, establish themselves as leaders of the Resistance, a hidden community of teenagers like themselves.
Originally published: New York : Little, Brown, 2010.